Building Brand Trust by Increasing Brand Awareness, Shaping Brand Image, and Engaging Brand Ambassadors - Tresia Deanra; Prida Ariani Ambar Astuti (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2024)
The role of branding is vital for companies striving to establish and nurture consumer trust. Developing a strong brand image and fostering trust involves various strategic approaches, including the use of influential brand ambassadors and increasing overall brand awareness. This study specifically focuses on evaluating the impact of brand ambassadors Vincent and Desta, as well as the level of brand awareness, on brand trust. In this context, brand image serves as an important intermediary factor. Adopting a positivistic paradigm combined with a quantitative research approach, this study utilizes an explanatory survey methodology directed at Instagram followers of @oronaminc.id. Following data collection, the information is meticulously processed with the SEM-PLS technique for comprehensive analysis. The findings reveal that the presence of brand ambassadors does not exert a direct and statistically significant influence on brand trust; however, their effect becomes significant when mediated through brand image. In contrast, brand awareness demonstrates a robust direct influence on brand trust and significantly contributes to enhancing brand trust through the intermediary of brand image. These insights underscore the importance of both awareness and image in effectively building brand trust within the competitive landscape of consumer beverages.